2016
DOI: 10.1680/jtran.14.00089
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting volume for U-turns at uncontrolled median openings

Abstract: This paper proposes a practical approach to estimate the conflicting traffic volume caused by U-turns at uncontrolled median openings under mixed traffic conditions. Data were collected at 21 median openings on multi-lane divided roads in India (i.e. 13 on six-lane and eight on four-lane). The road width at the median opening is divided into three parts: zone of severe conflict, zone of safety and unaffected zone based on the placement of the left wheel of U-turning vehicles (left-hand drive rule followed in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, they ignored the influence of the approaching through traffic volume and did not consider the influence of the temporal conflict factor for the estimation of conflicting traffic volume. Furthermore, for identifying the zone of safety, the methodology proposed by Mohapatra et al ( 13 ) requires the simultaneous arrival of both a U-turning vehicle and approaching through vehicle at the merging line, which is a demanding task because observation of the simultaneous arrival of both vehicles at an MBMO area requires data collection over a very long period. The methodology for the estimation of conflicting traffic volume proposed by Mohapatra et al ( 13 ) may therefore provide inaccurate results, which could result in incorrect estimation of U-turn capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they ignored the influence of the approaching through traffic volume and did not consider the influence of the temporal conflict factor for the estimation of conflicting traffic volume. Furthermore, for identifying the zone of safety, the methodology proposed by Mohapatra et al ( 13 ) requires the simultaneous arrival of both a U-turning vehicle and approaching through vehicle at the merging line, which is a demanding task because observation of the simultaneous arrival of both vehicles at an MBMO area requires data collection over a very long period. The methodology for the estimation of conflicting traffic volume proposed by Mohapatra et al ( 13 ) may therefore provide inaccurate results, which could result in incorrect estimation of U-turn capacity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Capacity estimation for U-turn requires three important parameters, namely: conflicting flow rate, critical gap, and follow-up time ( 8 , 11 , 12 ). Estimation of conflicting flow rate is most challenging pertaining to the peculiar traffic condition prevailing in developing economies in general and India in particular ( 13 ). Liu et al ( 12 ) carried out a study in the United States of America on a six-lane road and reported conflicting traffic volume as 2.2 times approaching traffic volume in each lane.…”
mentioning
confidence: 99%
“…A geometrical augmentation required at the median opening was suggested. Mohapatra et al in [5] also said that the conflicting traffic on six-lane roads was found to be relatively low, but on fourlane roads, almost all of the opposing traffic becomes conflicting traffic for U-turns.…”
Section: Introductionmentioning
confidence: 97%
“…MBMOs are provided in the raised median to vehicles to make a U-turn and reverse their flow direction (6). A U-turn maneuver is possible only if the desired gap of the U-turning driver is available in approaching through traffic (ATT) stream.…”
mentioning
confidence: 99%